A new species of Rhithrogena Eaton, 1881 from the Far East of Russia with notes on this genus in this area (Ephemeroptera: Heptageniidae) - Tiunova, Tatiana M. (Zootaxa, 2010)
Rhithrogena klugei sp. nov. (male, female and larva) are described from Far East of Russia. The Far Eastern species of Rhithrogena belong to two groups: lepnevae and sibirica. The species group sibirica is represented by the East Palaearctic species R. sibirica Brodsky 1930. The lepnevae species group includes R. lepnevae Brodsky 1930, R. bajkovae Sowa 1973 and R. klugei sp. nov. in the Far East and Siberia, and two species which can be found in the Russian Far East, R. piechockii Braasch 1977 from Mongolia, and R. ingalik Randolph and McCafferty 2005 from Alaska. The species group sibirica differs from lepnevae species group in that its larvae present a rounded projection on gills II–VI on the posterior-dorsal margin, whereas the imagines present a shoot at the base of the penis lobes. The larva of R. klugei sp. nov. differs from those of R. bajkovae and R. lepnevae in their form of gill I and in the ratio of the length to the width of gills III–IV. The male imago of the new species can be distinguished from others of the lepnevae species group by the absence of the latero-dorsoventral tooth on the penis lobes.